Analisa Pembebanan Interkoneksi Pada Penyulang Pangkur, Penyulang Tawun, Penyulang Muneng Menggunakan Software ETAP - Habsari, Kumala Mahda; Mashuri, Ibnu Ali; Fitri, Maratus Shalikhah Nur (SinarFe7, 2025)
Energy losses in the electricity distribution network are a problem that can cause losses, both from a technical and economic perspective. Losses or power losses are energy lost during the distribution process, the difference between the energy sent and the energy received. Losses are divided into two, namely technical and non-technical losses. Losses can be caused by losses, but losses can be suppressed or minimized. One method to reduce losses is load shedding, which is transferring part of the load to another feeder to obtain an optimal loss value. The interconnection between the Pangkur Feeder, Tawun Feeder, and Muneng Feeder requires efforts to minimize the loss value by gradually shifting the exiting Load Break Switch (LBS). The simulation results show that after load shedding, active power losses are reduced from 454.3 kW to 434.2 kW with a loss reduction of 20.1 kW. Meanwhile, reactive power losses decreased from 448.5 kVAR to 412.8 kVAR, with a loss reduction of 35.7 kVAR. From these results, it can be concluded that the load-sharing strategy through optimizing the LBS position is able to reduce the total losses of the interconnection network, thereby increasing the efficiency of electric power distribution